Blood and urinary biomarkers of prenatal exposure to disinfection byproducts and oxidative stress: A repeated measurement analysis. (April 2020) - Liu, Chong; Wang, Yi-Xin; Chen, Ying-Jun; Sun, Yang; Huang, Li-Li; Cheng, Ying-Hui; Liu, Er-Nan; Lu, Wen-Qing; Messerlian, Carmen
Highlights: 4150 blood and 4232 urine samples were collected from 1748 pregnant women. Urinary 8-OHdG, HNE-MA and 8-isoPGF2α varied greatly across pregnancy. Blood THMs were positively associated with urinary 8-OHdG and HNE-MA. Urinary HAAs were positively associated with 8-OHdG, HNE-MA, and 8-isoPGF2α . Abstract: Background: Toxicological studies have demonstrated that disinfection by-products (DBPs) can induce oxidative stress, a proposed mechanism that is relevant to adverse birth outcomes. Objective: To examine the associations of blood trihalomethanes (THMs) and urinary haloacetic acids (HAAs) with urinary biomarkers of oxidative stress among pregnant women. Methods: From 2015 to 2017, a total of 4150 blood and 4232 urine samples were collected from 1748 Chinese women during pregnancy. We determined concentrations of 4 blood THMs [chloroform (TCM), bromodichloromethane (BDCM), dibromochloromethane (DBCM), and bromoform (TBM)] and 2 urinary HAAs [dichloroacetic acid (DCAA) and trichloroacetic acid (TCAA)]. The summary measures of exposure for brominated THMs (Br-THMs; a molar sum of BDCM, DBCM, and TBM) and total THMs (TTHMs; a molar sum of TCM and Br-THMs) were also calculated. Associations of categorical (i.e., tertiles) and continuous measures of DBPs with urinary concentrations of oxidative stress (OS) biomarkers, 8-hydroxy-2-deoxyguanosine (8-OHdG), 4-hydroxy-2-nonenal-mercapturic acid (HNE-MA), and 8- iso -prostaglandin F2α (8-isoPGF2α ), were assessed using linear mixed regression models. Results: After adjusting for relevant confounding factors, we observed positive dose-response relationships between blood Br-THM tertiles and urinary HNE-MA ( P for trend < 0.001). We also found positive associations between tertiles of blood TCM and TTHMs and urinary 8-OHdG and HNE-MA (all P for trend < 0.05). Urinary HAAs were also positively associated with 8-OHdG, HNE-MA, and 8-isoPGF2α in a dose-response manner (all P for trend < 0.001). These associations were further confirmed when we modeled DBP exposures as continuous variables in linear mixed regression models, as well as in penalized regression splines based on generalized additive mixed models. Conclusions: Exposure to DBPs during pregnancy may increase maternal OS status.